British Foreign Policy and the National Interest
XI, 278 p.
Keywords: Whose interests does British foreign policy serve? Is the national interest a useful explanatory tool for foreign policy analysts? This interdisciplinary collection responds to these questions exploring ideas of Britain's national interest and their impact on strategy, challenging current thinking and practice in the making of foreign policy.